Individually - oriented a marching during study of natural-science disciplines - a basis of forming of professional competence of the future teacher of physical training. - Omelchuk O.V (Kharkov National Pedagogical University, 2010)
Directions of forming of professional competence of the future teachers are construed during study of natural-science disciplines. It is revealed, that in individually - oriented training one of the most efficient forms of preparation training is. Training is considered as the scheduled process of refilling of skills, knowledge, checks of the relation, idea, conduct. It is indicated, that the procedure of training rests on capabilities, tendencies, interests, valuable orientations, subject experience. She ensures intellectual development which affects in educational reachings.